2017
DOI: 10.1039/c7ob00205j
|View full text |Cite|
|
Sign up to set email alerts
|

Metal-free oxidative ring contraction of benzodiazepinones: an entry to quinoxalinones

Abstract: A novel and practical synthesis of 3-benzoylquinoxalin-2(1H)-ones from benzodiazepin-2-ones in two steps from commercially available starting materials is reported. The reaction was achieved in the presence of N-bromosuccinimide in DMSO which served both as a solvent and an oxidant. Significantly, the yet unknown ketone to alcohol fluorescence turn-on of benzoylquinoxalinones was unveiled through the preparation of a fluorescently labelled cholesterol conjugate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…After optimizing of the reaction conditions, the corresponding products 3 a-d were obtained using K 2 CO 3 (3 equiv) in DMF (Scheme 2) with good yields (71-85 %). [18] The 1 H-NMR spectrum showed the presence of two broad singlets at 5.13 and 5.28 ppm in the case of the compound 3 a (R 1 = Me) which attributed to the methyl moiety at the Nposition. In addition, the two protons of the methylene at αposition of the carbonyl of the compound 3 appear in the form of two singlets.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…After optimizing of the reaction conditions, the corresponding products 3 a-d were obtained using K 2 CO 3 (3 equiv) in DMF (Scheme 2) with good yields (71-85 %). [18] The 1 H-NMR spectrum showed the presence of two broad singlets at 5.13 and 5.28 ppm in the case of the compound 3 a (R 1 = Me) which attributed to the methyl moiety at the Nposition. In addition, the two protons of the methylene at αposition of the carbonyl of the compound 3 appear in the form of two singlets.…”
Section: Resultsmentioning
confidence: 94%
“…In this context, we have performed the O ‐alkylation using an alkyl halide. After optimizing of the reaction conditions, the corresponding products 3 a – d were obtained using K 2 CO 3 (3 equiv) in DMF (Scheme 2) with good yields (71–85 %) [18] …”
Section: Resultsmentioning
confidence: 99%
“…Yuan and Mao employed Cu 2 O and tert ‐butyl peroxybenzoate in the oxidative coupling of quinoxalin‐2(1 H )‐ones with alcohols to obtain the desired products [4] . Moreover, while the reduced derivatives of quinoxalin‐2(1 H )‐ones at the carbonyl groups could show fluorogenic properties (Figure 1), [5] the photophysical properties of these derivatives have been relatively overlooked, [6] with only a limited number of studies focusing on their fluorogenic properties having been reported to date [2c,5] . This is somewhat surprising, as these derivatives have potential utility as fluorogenic probes for the detection of valuable bioactive substances [5] .…”
Section: Figurementioning
confidence: 99%
“…Mtiraoui et al. synthesized 3‐benzoylquinoxalin‐2(1 H )‐ones from benzodiazepin‐2‐ones using a two‐step procedure with commercially available reactants . Imanishi et al.…”
Section: Introductionmentioning
confidence: 99%
“…[7] Mtiraoui et al synthesized 3-benzoylquinoxalin-2(1H)-ones from benzodiazepin-2-ones using a two-step procedure with commercially available reactants. [8] Imanishi et al demonstrated the synthesis of several quinoxalinones via a CuCl-catalyzed coupling 2-haloanilines with aminoacids followed by oxidation step. [9] Sanna et al reported the synthesis of quinoxalinones from a-keto acids or esters and benzene-1,2-diamine utilizing aqueous sulfuric acid as catalyst.…”
Section: Introductionmentioning
confidence: 99%